Geoid precision from limited‐area gravimetric surveys - Vermeer, Martin; Kollo, Karin (Geodesy and Cartography, 2012)
We derive a number of rough theoretical estimates for the precision of a geoid model computed from a local gravimetric survey combined with global reference model information. Example calculations for Finland and Estonia are presented. First published online: 03 Aug 2012